Geology and Potential Flash Flood Vulnerability of Sungai Jernih Village and Surroundings, Pondok Tinggi District, Kerinci Regency, Jambi: Geologi dan Potensi Kerawanan Banjir Bandang Desa Sungai Jernih dan Sekitarnya, Kecamatan Pondok Tinggi, Kabupaten Kerinci, Jambi - Viky Parmelian; Anggi Deliana Siregar; Yulia Morsa Said (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
Sungai Jernih Village and its surroundings have relatively steep slopes. Based on rainfall data for the last three years this area has moderate rainfall, with a tropical climate. In general, making the weathering level around it high and causing weathered soil/rock material conditions so that it is not strong retain the volume of water that is absorbed by the surface. The weathering can be carried away by water currents and flash floods. Pondok Tinggi sub-district has experienced flash floods, one of which was on May 13, 2017. The method used in this study is a direct mapping method, namely conducting field observations to map the distribution of lithology. Prior to field observations, analysis of secondary data obtained from literature studies and other sources was carried out to consider the results of field observations as a basic reference for research. Mapping results in the form of maps and parameter analysis using scoring overlaid with ArcGIS software. The low level of vulnerability with an area of ​​51.25% consists of 2 sub-districts, are in Pondok Tinggi District and Kumun District. The level of vulnerability is sufficient with an area of ​​25.39% consisting of 2 sub-districts are Sungai Bungkal District and Pondok Tinggi District. Then the highest vulnerability level with an area of ​​23.36% consists of 4 districts are Pesisir Bukit District, Sungai Bungkal District, Sungai Bungkal District Full and Pondok Tinggi District.